Anomalies and Investor Sentiment: International Evidence and the Impact of Size Factor - Salur, Bayram Veli; Ekinci, Cumhur (MDPI AG, 2023)
We examine whether investor sentiment can explain anomalies such as size and book-to-market in the US stock market. Differently from the literature, we test combination portfolios (portfolios formed on more than one factor such as size, book-to-market ratio, etc.) of developed markets for the same purpose. We find that sentiment is related to some anomalies in Europe, Japan, North America and global portfolios; hence, the sentiment and anomaly relationship may be universal. In addition, when size factor is controlled, the explanatory power of sentiment in anomaly returns changes.
Keywords: anomalies; investor sentiment; stock returns; stock returns; HG1-9999; investor sentiment; anomalies; Finance